WeChat online visual language among Chinese Gen Z: virtual gift, aesthetic identity, and affection language - Liu, Ruoxi (Frontiers in Communication, 2023)
Introduction: As a relatively new and innovative form of digital communication and visual image, emojis, emoticons, and stickers are appreciated, yet criticised. Young people on social media have lost the traditional social etiquette and interpersonal networking skills, which is a challenge in itself. This study provides a better understanding of how young people engage and behave in diverse interpersonal contexts while utilising digital visual language. Methods: This study contributes to digital anthography and social media studies, by conducting this study through interviews with 10 Generation Z young people from urban China and a 2-month-long participatory observation of three WeChat group chats. Results: By examining how young people use WeChat visual language in relationships with their elders or superiors, equivalent peers and intimate lovers or friends, this study found that emoticons and stickers become virtual gifts, aesthetic identities and the affection language of Generation Z. Discussion: This study contends that digital visual languages and new media do not alter human nature or ethical standards but rather provide new avenues for expression and empower human affective communication. Although the core of traditional etiquette is still being passed on and absorbed, its form has changed.